C-band and Ramac Shallow Radar Profiles Troll Station - South Pole (IPY 2007-2008) - Isaksson, Elisabeth; Kohler, Jack; Dens, Ruben (Norwegian Polar Institute, 2016)
The shallow radar measurements were made to obtain accumulation rates from the variation in depth to internal layers, and their lateral and temporal variability along the traverse route. The data were also collected for back-scatter comparison of the ground penetrating radars (GPR) and synthetic aperture radar (SAR). The overall goal of the comparison is to improve satellite- based estimations of accumulation rates. The ice flow velocities can be estimated from the morphology of internal layering evident in shallow radar data in areas of clear vertical structures in the firn column. These kind of structures can be found at the margins of the Recovery Lakes, for example. In addition, the radar data will be used to study firn properties together with the snow pit and firn core analysis. ### Route - Leg 1 (2007-2008): - **From:** Troll station [-72.01, 2.53] - **To:** "Camp Winter" [-86.8, 54.4] ### Instruments - **C-band radar**: A frequency-modulated continuous-wave (FMCW) system built by Svein-Erik Hamran. It has a center frequency of 5.3 GHz sweeping over a bandwidth of 1 GHz. The unambiguous range in air is 67.4 m with 451 samples in the frequency domain. - **Ramac 800 and 500 MHz**: RAMAC GPR device by Malå Geoscience is a commercial impulse radar that was operated with shielded 800 MHz and 500 MHz antennae. The 800 MHz antennae were used for the first part of traverse starting from Troll and ending at Site 91 in 2007/08, and the 500 MHz antennae were used from Site 91 to Camp Winter.